THE CHALLENGES FACED BY EFL PRE-SERVICE TEACHERS DURING ASISTENSI MENGAJAR PROGRAM - Wiediantin, Leony; Triana, Novita; Elyani, Eka Puteri (English Education Department, 2023)
The path to be an educator can be filled with difficulties, particularly for pre-service teachers enrolled in programs such as Asistensi Mengajar. The Asistensi Mengajar program, as a first step toward a teaching career, is critical in preparing undergraduate students from the Faculty of Teaching and Training for the demands and rigors of the educational landscape. This journey, however, is not without its challenges. Additionally, comprehensive studies investigating the challenges encountered by EFL pre-service teachers during the program are limited, considering the relatively new modifications implemented within the segment of the curriculum. These changes reflect broader trends in teacher education, which place a greater emphasis on practical experience, mentorship, and classroom management skills development. The result shows that there are four major area of the problems: 1) writing lesson plan 2) classroom management 3) preparedness and anxiety 4) positive working relationship with mentor teachers and peers. These challenges developed since they did not have much experience and teaching time as they were beginners. The results highlight the need for continual support, mentorship, and training to address these challenges and better prepare for the demands of the teaching profession. Additionally, to guarantee the comprehensive development of teaching abilities and competencies, a more comprehensive provisioning phase is required. Educational institutions and stakeholders should work to establish a supportive learning environment that fosters the growth and development of future educators.